2016
DOI: 10.1063/1.4953415
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two tetraalkylammonium ionic liquids. II. Phase transitions

Abstract: Phase transitions of the ionic liquids n-butyl-trimethylammonium bis(trifluoromethanesulfonyl)imide, [N1114][NTf2], and methyl-tributylammonium bis(trifluoromethanesulfonyl)imide, [N1444][NTf2], were investigated by differential scanning calorimetry (DSC), X-ray diffraction (XRD) measurements, and Raman spectroscopy. XRD and Raman spectra were obtained as a function of temperature at atmospheric pressure, and also under high pressure at room temperature using a diamond anvil cell (DAC). [N1444][NTf2] experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 52 publications
4
41
0
Order By: Relevance
“…1,5,10,11 Alkylammonium-based ILs have been studied well. 6,[13][14][15][16] Trialkylammonium ILs were extensively studied by Pott and Méléard 17 using X-ray scattering experiments, and by Shimizu et al 18 using molecular dynamics (MD) simulations. These studies reveal that the change in alkyl chain length strongly affects the structure, but it does not affect the intermediate and high-k peaks 17,18 obtained from X-ray experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,10,11 Alkylammonium-based ILs have been studied well. 6,[13][14][15][16] Trialkylammonium ILs were extensively studied by Pott and Méléard 17 using X-ray scattering experiments, and by Shimizu et al 18 using molecular dynamics (MD) simulations. These studies reveal that the change in alkyl chain length strongly affects the structure, but it does not affect the intermediate and high-k peaks 17,18 obtained from X-ray experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that the change in alkyl chain length has a signicant impact on segregation, diffusion, and domain formation. 15,16,[35][36][37] The simulations were further analyzed to get insight into the domain formation. The DMA molecules show different domain counts in different mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, N,N‐diethyl‐N‐methyl‐N‐(2‐ethoxyethyl)ammonium bis(trifluoromethylsulfonyl) imide does not crystallize neither upon cooling nor upon compression, although Raman spectra characteristic of different p – T regions remarkably differs in both the CH stretching region and below 450 cm −1 . Also ILs with a triflate anion, n‐butyl‐trimethylammoniumbis(trifluoromethanesulfonyl)imide and methyl‐tributylammonium bis(trifluoromethanesulfonyl)imide display different low‐temperature and high‐pressure phases . A combined study conducted by means of X‐ray diffraction and Raman spectroscopy on [bmim][PF 6 ] as a function of pressure and temperature evidenced a complex phase diagram with at least three crystalline phases, with different conformers distribution, structural arrangements, and disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Phase transitions have been identified by various methods: a slope change of the pressure dependence of some vibrational wavenumbers; the broadening of the fluorescence lines emitted from the ruby spheres used for measuring pressure; the appearance of a frozen dynamics below 100 cm −1 , in the case of glass transition; and the change in the population of different conformers of ions . As to the latter method, most studies were performed on ILs containing imidazolium‐based cations, which possess isomers, and anions, which do not possess conformers, such as BF 4 , PF 6 , NO 3 , and TfO .…”
Section: Introductionmentioning
confidence: 99%
“…Previous systematic studies of the conformers of the ions composing ILs have been reported for TFSI and PYR 14 [3,4,[12][13][14], bis(fluorosulfonyl)imide (FSI) [15][16][17], N,N-diethyl-N-methyl-N-propylammonium [18], imidazolium [11,[19][20][21][22], and ammonium ions [23,24]. It must be noted that the presence of different conformers can alter the physicochemical properties of ILs.…”
Section: Introductionmentioning
confidence: 99%